2022
DOI: 10.1093/ckj/sfac262
|View full text |Cite
|
Sign up to set email alerts
|

The metabolites ofde novoNAD+ synthesis are a valuable predictor of acute kidney injury

Abstract: Background AKI is often iatrogenic and potentially preventable. Reduced renal NAD+ is reported to increase the susceptibility of AKI. The present study explored the predictive value of urinary de novo NAD+ synthetic metabolites for AKI using two independent cohorts. Methods The expression of de novo NAD+ synthetic enzymes in human kidney was examined by immunohistochemistry and single-cell transcriptomes. Urine samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Given that KMO deficiency was reported to cause proteinuria in zebrafish and mice ( 37 ), we speculated that KMO is involved in the pathogenic mechanisms of DKD and explored the distribution of KMO in murine kidneys. In our study, KMO was predominantly expressed in proximal tubules, with the other two key enzymes of de novo NAD+ synthesis pathway, QPRT and HAAO, implying proximal tubules as active sites for de novo NAD+ synthesis to fulfill its high demand for energy consumption, consistent to present human data and our previous human study ( 24 ). KMO has also been reported in mice glomeruli, particular in podocyte ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Given that KMO deficiency was reported to cause proteinuria in zebrafish and mice ( 37 ), we speculated that KMO is involved in the pathogenic mechanisms of DKD and explored the distribution of KMO in murine kidneys. In our study, KMO was predominantly expressed in proximal tubules, with the other two key enzymes of de novo NAD+ synthesis pathway, QPRT and HAAO, implying proximal tubules as active sites for de novo NAD+ synthesis to fulfill its high demand for energy consumption, consistent to present human data and our previous human study ( 24 ). KMO has also been reported in mice glomeruli, particular in podocyte ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 92%
“…KMO was predominantly expressed in the cytoplasm of the proximal tubule, as evidenced by immunofluorescence analysis with Lotus tetragonolobus lectin (LTL) ( Figure 4B ). Moreover, QPRT and 3-hydroxyanthranilic acid oxygenase (HAAO), two other pivotal enzymes with predictive value of AKI in the de novo pathway ( 21 , 22 , 24 ), were also present in the same pattern. These observations indicated that the proximal tubule may serve as the primary site for the de novo synthesis pathway of NAD+ in the mouse kidneys.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations